Evaluation of bacterial activity in a structured bed reactor under different organic loading rates (OLR) - Aliberti, Edgar Augusto (2025)
This research aims to evaluate the bacterial activity response in a continuous upflow structured bed reactor for organic matter and nitrogen removal from dairy wastewater (with an initial concentration of 5,326 mg.L-1 of COD and 39 mg.L-1 of NH4+-N) under different organic loading rates (OLR). An acrylic bench-scale reactor with a total volume of 2.27 L and a working volume of 1.32 L was used and operated for 271 days. The reactor was operated in three experimental phases with different OLRs: Phase I - 1.2 kgCOD.m-3.d-1   (107 days); Phase II - 1.4 kgCOD.m-3.d-1  (94 days); and Phase III - 1.8 kgCOD.m-3.d-1  (70 days). During operation, COD removals above 90% were achieved in all phases. For nitrogen removal, the best results were obtained in Phase I, with average removals of TKN and total nitrogen (TN) of 81% and 74%, respectively. The increase in OLR affected nitrogen removal by directly interfering with the ammonification process. The ammonia-oxidizing bacteria (AOB) and nitrite-oxidizing bacteria (NOB) concentrations decreased with higher OLR. However, despite these results, no accumulation of oxidized nitrogen forms was observed, indicating that nitrification and denitrification occurred simultaneously. The structured bed reactor, operated with recirculation and intermittent aeration, proved effective for simultaneous organic matter and nitrogen removal, creating a stable and favorable environment for combined processes under different OLRs.